2022
DOI: 10.31680/gaunjss.1082535
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul ve Lise Öğrencilerinin Spora Yönelik Tutumlarının İncelenmesi

Abstract: Bu çalışmanın amacı; Batum Türk Okulu'nda eğitim-öğretim gören Ortaokul ve Lisede ye alan bireylerin, spora karşı ilgi durumlarının çeşitli demografik özellikler bakımından araştırılmasıdır. Bu doğrultuda araştırmaya 95 Kadın ve 97 Erkek, toplam 192 öğrenci gönüllü olarak katılmıştır. Batum Türk Okulu'nda yer alan öğrencilerin spora karşı tutumlarını belirlemek için öğrencilere Şentürk (2014), tarafından geliştirilmiş "Spora Yönelik Tutum Ölçeği" (SYTÖ), yüz yüze görüşme tekniği ile uygulanmıştır. Yapılan anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…Korer and Alpullu (2020) reported that the income levels of racketlon athletes were not adequate for anxiety and flow sub-dimensions. Unlike the research finding, Yapıcı et al (2022) reported a significant difference between the flow of life and leisure time of foreign nationals.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Korer and Alpullu (2020) reported that the income levels of racketlon athletes were not adequate for anxiety and flow sub-dimensions. Unlike the research finding, Yapıcı et al (2022) reported a significant difference between the flow of life and leisure time of foreign nationals.…”
Section: Discussioncontrasting
confidence: 96%
“…In parallel with this finding, studies conducted by Başçı and Gündoğdu (2011) to predict the attitudes of prospective teachers and Ustaoğlu et al (2020) to predict the attitudes of prospective physical education and sports teachers towards the creative drama course did not find a difference according to the gender variable. The study of Yapıcı et al (2022) revealed that gender did not affect the flow experiences of individuals participating in leisure time activities. Similarly, in the study of Demirel et al (2022), it was determined that gender did not affect the flow experience of individuals playing tennis for recreational purposes.…”
Section: Discussionmentioning
confidence: 93%
“…Nicel araştırmalarda normallik testi için verilerin basıklık ve çarpıklık değerlerine bakılarak karar verilebilmektedir. Nicel araştırmalarda normallik testi için verilerin basıklık ve çarpıklık değerlerini dikkate alan birçok çalışma mevcuttur (Ağtaş, Bektaş ve Güneri, 2019;Duman, Göksu, Köroğlu ve Talay, 2020;Yapıcı, Alpullu, Mametkulyyev ve Yılgın, 2022). Tabachnick ve Fidell (2013) normal dağılım için basıklık ve çarpıklık değerlerinin +1.5, -1.5 değerleri arasında olması gerektiğini belirtmektedir.…”
Section: Bulgularunclassified